Hubungan Kualitas Makanan dan Tingkat Stres dengan Sisa Makanan Lunak pada Pasien Rawat Inap di Rumah Sakit Karya Medika Tambun - Sifa Balaga; Sri Iwaningsih; Nur Setiawati Rahayu (UHAMKA PRESS, 2021)
Food waste is the volume or percentage of food that is not consumed and discarded as waste and is an impotant indicator to evaluate the effectiveness of food management and food service, as well as food patients food intake. Many factors cause food waste in patients in hospitals, incluiding psychological condition, age, type of disease, appearance of food, taste of food, etc. This study aims to determine the relationship betweenfood quality and stress levels with soft food waste in hospitalized patients in Karya Medika hospitals. This study was analytical with a cross sectional design. Sampling using purposive sampling technique consisting of 32 patient who received soft food. Data taken includes patient characteristic, food quality data, patient stress level data and patient soft food waste data. Processing data in this study using software with Chi Square. The results showed that the average residual food of respondents was as much as 12,7%. Statistical test results showed that there was no relationship (p = 0,152) between the appearance of food with leftovers from soft food. There was a relationship between food taste (p = 0,047) and stress level (p = 0,023) with soft food waste at Karya Medika Tambun Hospital . Keywords: food waste, food appereance, taste of food, stress levels.